ANALISIS IMPLEMENTASI PSAK 101 PADA LAPORAN KEUANGAN DI KSPPS BMT AL-BINA TASIKMALAYA - Naurah Nazhifah; Iwan Wisandani; Lina Marlina (Universitas Siliwangi, 2020)
This research, to study the implementation of PSAK 101 on the presentation and preparation of financial statements in KSPPS BMT Al-Bina Tasikmalaya. That is because at the BMT Al-Bina's financial statements found a non-conformity with PSAK 101 on the presentation of sharia financial statements. PSAK 101 is a statement of financial accounting standards that regulates the basic presentation of financial statement for sharia entities. This statement regulates the requirements for the presentation, structure and minimum requirements of the contents of financial statements. The method that used in this study is a qualitative descriptive method. Data collection technique in this research uses interviews, observation, and documentation to analyze data from the practice that carried out directly at the research site. The results of the study show that BMT Al-Bina in presenting they financial statements has not fully applied PSAK No.101, because (1) does not present a statement of cash flow, (2) does not present statement of sources and distribution of zakat (3) does not present statement of source and the use of virtue funds (4) does not present notes to financial statements (5) does not provide financial reporting and financial reporting information as required by PSAK No.101.